Analisis Tingkat Pengetahuan, Body Image dan Pola Makan terhadap Status Gizi Remaja Putri - Norma Jeepi Margiyanti (Universitas Baiturrahim, 2021)
Nutritional problems in adolescents arise due to incorrect nutritional behavior, namely the imbalance between the consumption of nutrients and the adequacy of recommended nutrients. The main nutritional problems in adolescents are micronutrients deficiency, especially iron deficiency anemia, as well as malnutrition problems, both malnutrition and short stature and more nutrition to obesity with co-morbidity which are both often related to wrong behavior / diet, namely the imbalance between nutritional consumption and nutritional adequacy recommended. The purpose of this research is to find out the relationship of knowledge, body image, and diet with the nutritional status of young women. This research method uses a descriptive approach to correlation, namely research conducted to look at the relationship between diet and nutritional status of young women. The results of the study were given P value= 0.016 which means there is a relationship between diet and nutritional status of young women. There is a relationship between the body image and the nutritional status of young women with P Value 0.000 and there is no relationship between the level of knowledge and the nutritional status of young women and P value of 0.083. Advice to stakeholders in order to be able to carry out a thorough socialization of nutrition in adolescents through promotional activities, increasing the capacity of health workers on adolescent nutrition and improving the implementation of the Youth Care Health Services (PKRR) program